Vaccination of elite athletes against SARS-CoV-2 and broader implications for public health policy - Sheehan, J. (OSF Preprints, 2022)
SARS-CoV-2, a human ß-coronavirus implicated as the causative agent in the COVID-19 pandemic, has been the subject of the most globally intensive vaccine development effort in recorded history. The spectrum of SARS-CoV-2 vaccine candidates, deployed globally, demonstrates an expansive diversity in regards to design philosophies and immunological mechanisms of action. In the context of an aging, physically deconditioned, and overweight global population, which finds itself heavily burdened by a high prevalence of non-communicable chronic disease; elite strength, power and endurance athletes represent a minority population comprised of extreme physiological outliers. This report explores the molecular toxicity and pathophysiology of the SARS-CoV-2 spike protein, the design and immunological strategies embodied by the spectrum of SARS-CoV-2 vaccine candidates, and the intersection of these phenomena with the demographic, lifestyle and physiological characteristics of elite athletes; so as to inform vaccination strategies against SARS-CoV-2 which most protect this outlying minority population.